2021
DOI: 10.1155/2021/6621772
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Level vs. Score-Level Fusion in the Human Identification System

Abstract: The design of a robust human identification system is in high demand in most modern applications such as internet banking and security, where the multifeature biometric system, also called feature fusion biometric system, is one of the common solutions that increases the system reliability and improves recognition accuracy. This paper implements a comprehensive comparison between two fusion methods, named the feature-level fusion and score-level fusion, to determine which method highly improves the overall sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Hence, using the same architecture to extract features (i.e., fusion at sensor-level) or process separately extracted features (i.e., fusion at featurelevel) in the context of fundamentally different data modalities (e.g., inertial and video data) may be more challenging than using the outputs of the individual models (i.e., fusion at scorelevel and decision-level). This may also explain why research in multimodal biometric identification systems found scorelevel fusion to be more promising than feature-level fusion [30]- [32]. However, further research needs to clarify whether score-level fusion of inertial and video data also outperforms sensor-level and feature-level fusion for intake gesture detection.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, using the same architecture to extract features (i.e., fusion at sensor-level) or process separately extracted features (i.e., fusion at featurelevel) in the context of fundamentally different data modalities (e.g., inertial and video data) may be more challenging than using the outputs of the individual models (i.e., fusion at scorelevel and decision-level). This may also explain why research in multimodal biometric identification systems found scorelevel fusion to be more promising than feature-level fusion [30]- [32]. However, further research needs to clarify whether score-level fusion of inertial and video data also outperforms sensor-level and feature-level fusion for intake gesture detection.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The matching scores (e.g., probability estimates) indicate the similarity between the input feature set and the ground truth. Comparison studies in multimodal biometric identification system [30]- [32] found score-level fusion to outperform feature-level fusion. Score-level fusion approaches can be broadly categorized into two groups [8].…”
Section: Figure 1 Different Levels Of Fusion Of Multi-modality Datamentioning
confidence: 99%
“…The first is PCA, which entails three steps: calculating eigenvalues, eigenvectors, and feature vector covariance matrices. These templates can be made smaller while still retaining the most critical features using an approach that combines feature extraction with dimension reduction 21 . To calculate PCA, the following formula is used: mean(A¯)=1ni=1nai,where ai is the pixel value in i and n is the total number of pixels in an image.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the fusion process is performed using the concatenation of different extracted feature pointsets as seen in Eq. 9 where the plus (+) symbol refers to that concatenation operation 54,55 .…”
Section: Features Fusionmentioning
confidence: 99%